Trade Policy Developments in Industrial Countries - Tseng, Wanda; Anjaria, Shailendra; Iqbal, Zubair; Perez, Lorenzo (Washington, D.C. : International Monetary Fund, 1981)
This study reviews recent developments in international trade policies in selected industrial countries. It was prepared for the June 1981 World Economic Outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet